Contemporary Innovative University as a Subject of State Youth Policy Implementation in the Russian Federation - Astvatsaturova, Maya Artashesovna; Kondrakova, Elvira Dmitrievna; Aslanovich, Zavrumov Zaur (International Review of Management and Marketing, 2016)
This paper is devoted to the implementation of state youth policy (SYP) of the Russian Federation (RF) at the contemporary stage which is marked with problems and contradictions caused by both external and internal challenges. SYP implementation is carried out by both direct policy and management subjects (state authorities and municipalities) and indirect parties – institutions, organizations, civil society institutions. Among indirect parties, the authors specify higher professional education institutions, first of all, innovative universities. In the course of educational and training process, many SYP principles are realized, not only students education in compliance with the state educational standards, but also training skills and experiences being a part of students’, masters’, PhD students’, young specialists’ civil positioning. Efficient part in SYP implementation is taken by the Pyatigorsk State Linguistic University (PSLU), realizing the original program PROFI – SOCI – LINGUA which enables young students to gain knowledge, skills and experience (including volunteering) of professionalism, social activity and public attendance. Keywords: state youth policy, sociocultural and sociomental view of youth, contemporary youth factor, innovative university JEL Classifications: I20; I23; I28